السياسة العامة للسكن في الجزائر ودورها في الحد من العشوائيات - مسلم دلال (جامعة المسيلة, 2022)
انتهجت الجزائر بعد تسعينات العقد الماضي سياسة سكنية تعتمد في مجملها على الدور الأساسي للدولة في الإنجاز والتسيير بما في ذلك التمويل والتوزيع ،ولقد قامت الدولة منذ هذه الفترة باتخاذ إجراءات مختلفة لإنعاش قطاع السكن كالتنويع في أنماط السكن الحضري باعتمادها على آليات مختلفة في تمويل المشاريع السكنية حيث صدرت تعليمات مختلفة غيّرت نمط تمويل السكن في كل فترة ،وقامت بإنشاء منظمات تسهر على تشجيع عرض السكن كالصندوق الوطني للسكن، وإشراك القطاع الخاص في السوق السكنية ،كما تم الاعتماد على نمط جديد وهو السكن عن طريق البيع بالإيجار. ورغم كل الاجراءات والمجهودات المبذولة من أجل النهوض بقطاع السكن ،إلا أن هذا الأخير عرف تفاقما في أوضاعه نتيجة عدم كفاية الموارد المالية ،وعجز قطاع البناء عن تأدية دوره في تغطية الاحتياجات من حيث الجودة والتكلفة بسبب قلة مواد البناء وارتفاع أسعارها ،بالإضافة إلى التدهور في الطاقة الانتاجية ،غير أنه أصبح من السهل تحديد مستوى هذا العجز خصوصا عندما يتعلق الأمر بربط الطلب على السكن بالقدرة الشرائية للمواطن إضافة إلى ضعف معدلات الادخار وعدم القدرة على الحصول على سكن لائق وذلك نظرا للارتفاع المتزايد في ثمن السكنات الموجودة بسبب ارتفاع تكلفة إنجازه ،إلى جانب النمو الديمغرافي السريع الذي أدى إلى زيادة الطلب على السكن وساهم بشكل كبير في تفاقم هذه الأزمة . الكلمات المفتاحية: السياسة العامة ،السياسة السكنية ،العشوائيات. Abstract: After the nineties of the last decade، Algeria adopted a housing policy that relies in its entirety on the primary role of the state in implementation and management، including financing and distribution. Various instructions were issued that changed the pattern of housing financing in each period، and they established organizations that watch over the promotion of housing، such as the National Housing Fund، and the involvement of the private sector in the housing market، and a new pattern was relied upon، which is housing through rental sales. Despite all the measures and efforts made to advance the housing sector، the latter has experienced an aggravation in its conditions as a result of insufficient financial resources، and the inability of the construction sector to fulfill its role in covering the needs in terms of quality and cost due to the lack of building materials and their high prices، in addition to the deterioration in energy Productivity، however، it has become easy to determine the level of this deficit، especially when it comes to linking the demand for housing with the purchasing power of the citizen، in addition to the weak saving rates and the inability to obtain decent housing due to the increasing increase in the price of existing housing due to the high cost of its implementation، in addition to the growth The rapid demographic that led to an increase in the demand for housing and contributed significantly to the exacerbation of this crisis. Keywords: public policy، housing policy، slums.
Keywords: السياسة العامة ،السياسة السكنية ،العشوائيات.